SANKSI PIDANA TERHADAP PENYALAHGUNAAN NARKOTIKA, GOL.1 DALAM BENTUK BUKAN TANAMAN UNTUK DIRI SENDIRI (PUT.NO.103/PID.SUS/2021/PN.JKT.SEL): Criminal Sanctions for The Abuse of Narcotics, Category 1 in The Form of Non-Plant For It Self - Wibowo, Bimo Ilham; Widjajanti, Ermania (Faculty of Law, Universitas Trisakti, 2024)
According to the National Narcotics Agency, drug abuse increased from 1.80% to 1.95% in 2021-2022. This has resulted in overcrowding in prisons. The majority of inmates in correctional facilities are drug offenders, estimated at 145,413 out of 151,303 individuals. This study discusses the case of Rahmat Handoyo, also known as Doyok, who committed the crime of